Palavra-performance - Alexandrini, Camila (2017)
This doctoral research titled Word-Performance has been developed out of the following areas: contemporary research on literature and performance. The dialogue between these two fields of analysis has proven to be exciting and promising, given that interdisciplinary research offers an unusual character to the literary. Many literary theorists use the word performance, or performative and performativity, as a concept to indicate the conduct, performance and behavior of certain literary, social, political forms. However, the performance here is first proposed as an investment to the availability of other spaces to what we call literature and therefore allow it to be understood, read and also developed via other theoretical methods. In this sense, from the relationship between the theory of literature and the other arts, because the performance is configured on the border between the performing, the visual and literary arts, has sought not only a dialogue with various theoretical contributions, but also provide another understanding of the literary text to the community academic as well as readers. Actually, a few years ago, even before the advent of technology, the literary text has reinvented itself through other media. In fact, what this study seeks to demonstrate is that the performance itself was always permitted to the reader, since the literature provokes more than just knowing something, it encourages us to go beyond the text itself, whether through singular marks in the course of reading, through the desire of understanding and responding to what is written, or by our own artistic action that comes from it. From this relationship a vast field of literary research and analysis is drawn, from which this thesis has been engaged in presenting a significant and qualified approach to contemporary research on literature. Beyond the complex and exciting contact with other arts, literature has much to reveal to researchers and readers.